2018
DOI: 10.1159/000493842
|View full text |Cite
|
Sign up to set email alerts
|

Juniperus Communis Extract Exerts Antitumor Effects in Human Glioblastomas Through Blood-Brain Barrier

Abstract: Background/Aims: Herbal materials derived from Juniperus communis (JCo) possess anticancer activity. In this study, we evaluated the efficacy of a JCo berry extract in suppressing glioblastoma growth. Methods: The effects of JCo extract on the viability of normal and glioma cell lines was analyzed using a modified 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. The synergistic therapeutic effect of JCo extract and temozolomide (TMZ) on glioma cells was examined by MTT analysis. Flow c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…On the other hand, the administration of J. communis essential oils (200 mg/kg) in BALB/c nude mice injected with HepG2 cancer cells showed the capacity to reduce tumor growth and extend the lifespan with no or low systemic and pathological toxicity [ 132 ]. Similar information was reported by Lai and colleagues [ 133 ] and Tsai and collaborators [ 135 ] regarding the antitumor effects of this plant against human colorectal adenocarcinoma and glioblastoma.…”
Section: Biological Potential Of Juniperus Communis ...supporting
confidence: 86%
See 1 more Smart Citation
“…On the other hand, the administration of J. communis essential oils (200 mg/kg) in BALB/c nude mice injected with HepG2 cancer cells showed the capacity to reduce tumor growth and extend the lifespan with no or low systemic and pathological toxicity [ 132 ]. Similar information was reported by Lai and colleagues [ 133 ] and Tsai and collaborators [ 135 ] regarding the antitumor effects of this plant against human colorectal adenocarcinoma and glioblastoma.…”
Section: Biological Potential Of Juniperus Communis ...supporting
confidence: 86%
“…On the other hand, essential oil and distilled extracts from J. communis berries revealed the potential to suppress A549 human lung adenocarcinoma epithelial-cell growth and development, revealing IC 50 values of 69.4 and 1270 µg/mL, respectively, after 24 h of treatment [ 71 ]. Additionally, they also showed the ability to suppress the development of SH-SY5Y human neuroblastoma cells after 24 h of exposure (IC 50 score of 53.7 µg/mL), which is evidence that this plant can penetrate the blood–brain barrier [ 134 , 135 , 142 ]. The capacity of J. communis plant material (twigs, leaves and berries) to suppress NCI-H460 lung carcinoma, MCF-7, AGS gastric carcinoma, and Caco-2 cell growth was also evaluated, revealing IC 50 values varying depending on the origin [ 75 ].…”
Section: Biological Potential Of Juniperus Communis ...mentioning
confidence: 99%
“…The hydroalcoholic extract obtained from J. communis has genoprotective, antioxidant, antifungal and antiinflammatory properties (Fierascu et al 2018). The research results showed that J. сommunis extract successfully penetrates the blood-brain barrier and effectively inhibits the growth of glioma cells (Tsai et al 2018).…”
Section: Fabаceae Familymentioning
confidence: 99%
“…Methanolic extracts of J. communis leaves have been found to block the growth and development of C6 rat-brain tumor and HeLa human-cervix carcinoma cells, PC3 humanprostate cancer cells, HCT 116 human-colon cancer cells, and MCF7 breast cancer cells. Essential oil and extracts from J. communis berries have also been found to suppress A549 human lung adenocarcinoma epithelial cells' growth and development, as well as suppress the development of SH-SY5Y human neuroblastoma cells [330,331].…”
Section: Role Of Wild Plants In Cancer Prevention and Treatmentmentioning
confidence: 99%